The impact of Quality of Life Programs at work in times of crisis (Research, Society and Development, 2021)
Work is part of man's nature and, through this, people build the world and themselves, with a personality and subjectivity inherent to each aspect, therefore, having quality in the exercise of the same becomes essential, gaining prominence before the pandemic of coronavirus experienced today. That said, this paper aims to address the issue of Quality of Working Life (QWL) through the organizational crises, having as one of the focuses the situation caused by the economic crisis and also the pandemic of the new coronavirus (COVID-19), which comprehensively reached the world of work. This paper used the methodology bibliographic research, with a qualitative approach. Quality serves so that both societies and companies can achieve their goals of economic growth and development, as well as achieving a better and more satisfying standard of living. It is concluded that developing QWL programs becomes a necessary challenge, as it is in this juncture that professional development becomes essential, including for economic recovery in companies, maintaining the quality of life of the greatest capital it has: the human.